Zbtb1 controls NKp46(+) ROR-gamma-T(+) innate lymphoid cell (ILC3) development - Lu, Ying (Oncotarget, 2017)
Innate lymphoid cells (ILCs) play a central role conferring protection at the mucosal frontier. In this study, we have identified a requirement of the transcription factor Zbtb1 for the development of RORγt(+) ILCs (ILC3s). Zbtb1-deficient mice lacked NKp46(+) ILC3 cells in the lamina propria of the small and large intestine. This requirement of Zbtb1 was cell intrinsic, as NKp46(+) ILC3s were not generated from Zbtb1-deficient progenitors in bone marrow chimeras and Zbtb1-deficient RORγt(+) CCR6(−)NKp46(−) ILC3s didn't generate NKp46(+) ILC3s in co-cultures with OP9-DL1 stroma. In correlation with this impairment, Zbtb1-deficient ILC3 cells failed to upregulate T-bet expression, and to acquire IFN-γ production characteristic of NKp46(+) cells. Finally, absence of NKp46(+)ILC3 cells combined with the absence of T-cells in Zbtb1-deficient mice, led to a transient susceptibility to C. rodentium infections. Altogether, these results establish that Zbtb1 is essential for the development of NKp46(+) ILC3 cells.